Complex Composite Odontoma: A Cause of Impacted Teeth - Satya Ranjan Misra (Institute of Medico-legal Publications Pvt Ltd, 2020)
Odontomas are one of the most common odontogenic lesions, earlier considered as mixed odontogenicneoplasms but lately have been accepted as hamartomatous malformations. They are either detectedaccidentally on radiographs or when they are a cause of impeding normal eruption of teeth. Odontomasoriginate from the odontogenic tissue and contain enamel and dentine, hence are referred to as compositelesions. They can be of two types depending on the appearance. If they have masses of calcified structuresresembling multiple miniature teeth then they are called compound odontomas and if they appear as anirregular disorganized radiopaque mass they are referred to as complex odontomas. A case if complexodontoma is reported herewith which led to impacted maxillary molar.